Profile of Intravenous Preparation Mixing in Patients at the Regional General Hospital's Intensive Care Unit Abdoel Wahab Sjahranie Samarinda (Sciences of Pharmacy, 2022)
Compatibility is one of the quality characteristics of intravenous (IV) preparations that influences the effectiveness of patient therapy in the Intensive Care Unit (ICU). The purpose of this study was to determine the compatibility profile of IV medication formulations given to ICU patients. This prospective observational research was undertaken on patients in the ICU of a private hospital in Samarinda. The data on intravenous combination of drugs were compared in this study utilizing the ASHP Injectable Drug Information literature 21st edition, Injectable drug guide, and Manual Book. Injectable Drug Mixing was published in 2009 as a resource for determining the compatibility of intravenous formulations. Using certain criteria, combinations of intravenous medicines and their solvents are classed as compatible (C), incompatible (I), and unknown (U). The ICU had 25 patients, 15 of whom were male and 10 of them were female. There is no mixing of drug compounds containing incompatible solvents. All drugs were carried out with 100% compatible solvents. The limited information related to the compatibility and stability of these intravenous preparations encourages continuous monitoring of the patient's condition and drug levels.